K analýze deontických modalít v Transparentnej intenzionálnej logike - Glavaničová, Daniela (Organon F, 2015)
The aim of this paper is to outline a suitable analysis of certain deontic modalities. To avoid confusion as much as possible, I specify the subject-matter of my analysis explicitly. Subsequently, the paper argues that Transparent Intensional Logic (TIL) is an appropriate framework for developing deontic logic. The main contribution of the paper consists in a proposal concerning the analysis of deontic modalities in TIL as well as in offering a semantically based distinction between implicit and explicit deontic modalities. Finally, I introduce some definitions along with some inferential rules and show (using Ross’ paradox) how it is possible to deal with the paradoxes of deontic logic in terms of my analysis.
Keywords: Analysis; deontic modalities; descriptive versus prescriptive; implicit versus explicit; paradox; transparent intensional logic